Effect of Varied Degumming Concentrations on Soap from Used Cooking Oil - Hafiz, Ahmad; Ibrahim, Siti Aida (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Reused cooking oil is an edible oil that was formerly used for frying but is no longer suitable for consumption. Used cooking oil can pose a threat to the environment if not handled properly. This research aimed to produce a bar soap from treated used cooking oil using cold process while investigating the physicochemical properties of the bar soap by varying the concentration of sulfuric acid during the degumming process. For that purpose, used cooking oil around Taman Permai were collected and treated via degumming at 90°C at 3000 rpm using three different concentrations of sulfuric acid which is 0.2%, 0.4% and 0.6% v/w. The treated oil was then used as a primary material in soap making by mixing it with sodium hydroxide and distilled water using cold process. It was found that the pH level and the texture of the soap made from treated used cooking oils are similar to new cooking oil. However, the result shows that all the soap achieves similar cleaning ability. It can be concluded that the oil refinery process helps in improving the physical appearance of the oil and soap but no significant differences in cleaning power. As for the samples, sample CT3 has the softest texture and aesthetically better than the other two treated soaps while having similar cleaning power.